An introduction to econometrics - Klein, Lawrence R. (Englewood Cliffs, N.J. : Prentice-Hall, 1962)
The book covers: Statistical demand analysis; Statistical production and cost analysis; The Distribution of income and wealth; Statistical models of economic growth and trade cycles; Applications in macroeconomics. The book is for both graduate and undergraduate students who show intense interest in finding out what econometrics is all about, but lack the mathematical equipment to understand most renditions of the subject.
Includes bibliographical footnotes.
rpm 22/09/2017
Loans
Keywords: Economics, Mathematical; Econometrics